A double-masked evaluation of lignocaine-prilocaine cream (EMLA) used to alleviate the pain of retrobulbar injection. Issue 3 (March 1991) - Sunderraj, P; Kirby, J; Joyce, P W; Watson, A
Abstract : A randomised, placebo controlled, double-masked study was undertaken in 115 patients undergoing cataract surgery to assess the efficacy of the anaesthetic cream EMLA (eutetic mixture of local anaesthetic, lignocaine-prilocaine) in alleviating the pain of retrobulbar injection. Sixty three patients received the EMLA cream and 52 the placebo cream. The pain was assessed objectively by the anaesthetist, who observed the reaction of the patient on needle insertion, and subjectively by the patient. Significantly lower pain scores were recorded in patients treated with EMLA cream (anaesthetist's observation: p less than 0.01, patient's assessment: p less than 0.006). No patients experienced serious side effects in either treatment group.